2009
DOI: 10.1097/bsd.0b013e31817e6fa8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Computed Tomography and Plain Radiography in Assessing Traumatic Spinal Deformity

Abstract: Screening CT demonstrates excellent correlation with plain radiography for measuring thoracolumbar spinal deformity in the coronal and sagittal planes for patients with trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Although easy to recognise and well-defined diagnostic criteria were used to recognise thoracic vertebral body malformations, spinal kyphosis and spinal scoliosis, little is known on how both imaging modalities compare for these specific purposes. Several studies in human medicine have compared radiography vs. CT [ 31 , 32 ] and radiography vs. MRI [ 33 , 34 ] to evaluate and quantify spinal curvature abnormalities, while only a few studies have compared all three imaging techniques for this purpose [ 35 , 36 ]. The results of these studies indicate that CT and MRI can be used to evaluate and quantify spinal curvature abnormalities with a good reliability, correlation and agreement among the three imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Although easy to recognise and well-defined diagnostic criteria were used to recognise thoracic vertebral body malformations, spinal kyphosis and spinal scoliosis, little is known on how both imaging modalities compare for these specific purposes. Several studies in human medicine have compared radiography vs. CT [ 31 , 32 ] and radiography vs. MRI [ 33 , 34 ] to evaluate and quantify spinal curvature abnormalities, while only a few studies have compared all three imaging techniques for this purpose [ 35 , 36 ]. The results of these studies indicate that CT and MRI can be used to evaluate and quantify spinal curvature abnormalities with a good reliability, correlation and agreement among the three imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…2 The major disadvantage of radiographic films is their inability to detect ligamentous injuries. 38 Measurement of posttraumatic kyphotic angulation is useful for assessment of fracture progression, especially for fractures managed conservatively. Kyphotic angulation is measured as the angle between the superior end plate one level above and the inferior end plate one level below the injured segment.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…CT is ideal for imaging complex fractures and determining the degree of vertebral comminution. 38 More complex imaging modalities, such as CT myelography and magnetic resonance imaging (MRI) are not necessary unless the patient has a neurologic deficit. In special cases where the compression fracture is because of an infectious or malignant process, more advanced MRI techniques can be used.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…When the patient is lying down during an MRI examination, the patient's back muscles can be completely relaxed, and the protective anteversion brought on by discomfort can also be reduced. Due to the short examination time, these factors cannot be completely eliminated in CT examination [22]. Kaiser R et al [23] found a linear dependency between hyperextension radiograph and MRI exibility with a mean difference of 9.3° (R 2 = 0.61, p < 0.001) by using the imaging data of 18 Scheuermann kyphosis patients.…”
Section: Discussionmentioning
confidence: 99%